Toll-like receptor 7/8 agonist R848 alters the immune tumor microenvironment and enhances SBRT-induced antitumor efficacy in murine models of pancreatic cancer. Issue 7 (17th July 2022) - Ye, Jian; Mills, Bradley N; Qin, Shuyang S; Garrett-Larsen, Jesse; Murphy, Joseph D; Uccello, Taylor P; Han, Booyeon J; Vrooman, Tara G; Johnston, Carl J; Lord, Edith M; Belt, Brian A; Linehan, David C; et al.
Abstract : Background: Stereotactic body radiotherapy (SBRT) has been increasingly used as adjuvant therapy in pancreatic ductal adenocarcinoma (PDAC), and induces immunogenic cell death, which leads to the release of tumor antigen and damage-associated molecular patterns. However, this induction often fails to generate sufficient response to overcome pre-existing tumor microenvironment (TME) immunosuppression. Toll-like receptor (TLR) 7/8 ligands, such as R848, can amplify the effect of tumor vaccines, with recent evidence showing its antitumor effect in pancreatic cancer by modulating the immunosuppressive TME. Therefore, we hypothesized that the combination of R848 and SBRT would improve local and systemic antitumor immune responses by potentiating the antitumor effects of SBRT and reversing the immunosuppressive nature of the PDAC TME. Methods: Using murine models of orthotopic PDAC, we assessed the combination of intravenous TLR7/8 agonist R848 and local SBRT on tumor growth and immune response in primary pancreatic tumors. Additionally, we employed a hepatic metastatic model to investigate if the combination of SBRT targeting only the primary pancreatic tumor and systemic R848 is effective in controlling established liver metastases. Results: We demonstrated that intravenous administration of the TLR7/8 agonist R848, in combination with local SBRT, leads to superior tumor control compared with either treatment alone. The combination of R848 and SBRT results in significant immune activation of the pancreatic TME, including increased tumor antigen-specific CD8 + T cells, decreased regulatory T cells, and enhanced antigen-presenting cells maturation, as well as increased interferon gamma, granzyme B, and CCL5 along with decreased levels of interleukin 4 (IL-4), IL-6, and IL-10. Importantly, the combination of SBRT and systemic R848 also resulted in similar immunostimulatory changes in liver metastases, leading to improved metastatic control. CD8 + T cell depletion studies highlighted the necessity of these effector cells at both the local and hepatic metastatic sites. T cell receptor (TCR) clonotype analysis indicated that systemic R848 not only diversified the TCR repertoire but also conditioned the metastatic foci to facilitate entry of CD8 + T cells generated by SBRT therapy. Conclusions: These findings suggest that systemic administration of TLR7/8 agonists in combination with SBRT may be a promising avenue for metastatic PDAC treatment.